KOHESI GRAMATIKAL DAN LEKSIKAL PADA LIRIK LAGU “KITA” GROUP BAND SHEILA ON 7 - Pramitasari, Afrinar (Universitas Hamzanwadi, 2022)
This study aims to describe (1) how the form of grammatical cohesion in the lyrics of the song